Prawa i obowiązki stron umowy licencyjnej dotyczącej wzorów przemysłowych w świetle regulacji krajowych i Unii Europejskiej - Skrzypczak, Jędrzej (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
The paper analyzes the rights and responsibilities of the parties of license agreements concerning industrial providd for in Polish and EU regulations. In particular, it attempts to answer the question whether the licensee’s commissioning of manufacturing activities may infringe on the license conditions. It is proposed here that such licensee conduct is covered by the extent of the license provided that the licensee is in charge of organizing the manufacturing process and solely decides about the principles, conditions and the scale of production; he retains the ownership right to the product manufactured; the product is introduced under the licensee’s own brand; the licensee actually decides about the principles under which the product is launched on the market, including the complete, independent and unlimited freedom of deciding about the commercial conditions concerning the price, markup and term of payment; and the licensee bears full responsibility for the quality of the commodity entered into the market whereas the role of the contractor is limited to the performance of technical activities related to the manufacturing of the product protected by the indial.